Aboriginalities - Biasino, Fabrice; Dom, Myriam; Stouffs, Julie; Cook, Paula (Royal Museums of the Fine Arts of Belgium, 2021)
"Aboriginalities" immerses you into the fascinating universe of Aboriginal painting - an art form that is both ancestral and contemporary, always rooted in spirituality. Far more than a simple physical and sensory experience, Aboriginal art invites us to rethink our connection to the earth and the universe. As a window on the spiritual, Aboriginal art tells the story of the creation of the world - called "Dreamtime"* - and the original link between humans and the earth. The numerous motifs (dotted lines, spirals, zigzags, crosshatching...) are passed down from generation to generation by members of the same community, concealing centuries-old secrets as well as a map of their territory. This ancestral and highly symbolic art form was originally concealed: drawn in the sand or applied on rocks on territories forbidden to laypersons. But in the early 1970s, amidst struggles for the recognition of an Aboriginal identity, the Papunya Tula community translated their cultural practices and symbolic knowledge through paint. Using non-traditional methods borrowed from Western culture (acrylics, brushes, cardboard and later canvas), the indigenous people of Australia found a modern way to express their cultural, political, social and economic struggles. Vibrant and colourful, the exhibition "Aboriginalities" is built around part of the private collection of Marie Philippson, who has been passionate about modern culture and Aboriginal art for over 20 years. The exhibition shows over 120 paintings and objects, reflecting the extraordinary formal inventiveness of Aboriginal artists. At several intersections throughout the exhibition, a dozen works from the RMFAB's modern art collection echo the subjects addressed by these "Dreamtime" artists, questioning our relationship to the visible and the invisible. Exhibition: Koninklijke Musea voor Schone Kunsten, Brussels, Belgium (01.04. - 01.08.2021)
Catalog of an exhibition held at the Koninklijke Musea voor Schone Kunsten, Brussels, Belgium from April 1 - August 1, 2021
Keywords: Geschichte 1992-2019; Indigenes Volk; Malerei; Aborigines; Australien; Painting, Aboriginal Australian / Exhibitions; Art, Aboriginal Australian / Exhibitions; 1900-2099; Exhibition catalogs; Ausstellungskatalog -- Royal Museums of the Fine Arts of Belgium -- 01.04.2021-01.08.2021 -- Brüssel